2002
DOI: 10.1002/etc.5620210625
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of reactive sulfide on the acute toxicity of silver (I) to Daphnia magna. Part 1: Description of the chemical system

Abstract: Experiments were designed to assess the potential protective effect of the presence of sulfide against the acute (48-h) toxicity of silver(I) to Daphnia magna. Tests were conducted in borosilicate glass beakers (250 ml) in moderately hard synthetic water. Toxicity solutions were replaced after 24 h by static renewal method. This paper describes the chemical system, and the acute toxicity results are presented in a companion paper. Sulfide was below detection limit (<5 nM) in controls with no sulfide added. Sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 22 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…These methods can affect the surface reactivity and ion outlet in order to avoid any cytotoxic occurrence. One of the coating and surface passivation methods is sulfidation, for example, the existence of sulfide can avoid AgNO 3 toxicity ( Bowles et al, 2002 ). Also, Levard et al (2013) reported that sulfidation of silver NPs can hinder Ag ion mobility and reduce its dissolution rate.…”
Section: Toxicity Of Common Metallic and Metal Oxide Npsmentioning
confidence: 99%
“…These methods can affect the surface reactivity and ion outlet in order to avoid any cytotoxic occurrence. One of the coating and surface passivation methods is sulfidation, for example, the existence of sulfide can avoid AgNO 3 toxicity ( Bowles et al, 2002 ). Also, Levard et al (2013) reported that sulfidation of silver NPs can hinder Ag ion mobility and reduce its dissolution rate.…”
Section: Toxicity Of Common Metallic and Metal Oxide Npsmentioning
confidence: 99%